Exploring of new age-related CpGs using Methbank database and the pyrosequencing. Issue 1 (December 2019) - Xie, Bowen; Wang, Shuangshuang; Xie, Mingkun; Luo, Haibo; Zhang, Ke; Zhao, Huan; Song, Feng; Huang, Yun
Abstract: In crime scenes, age prediction of biological stains could be of great significance in searching the suspects and reconstructing the events. Age-related CpGs (AR-CpGs) has been increasingly recognized because of its potential application for forensic age prediction. Currently, the MethBank database with 34 consensus reference methylomes from 4577 human blood samples was available. The current study aimed to develop a strategy for screening out the AR-CpGs markers based on both MethBank database and the pyrosequencing methods. Four AR-CpGs were selected for DNA methylation analysis in Chinese Han population. Twenty blood stains which were stored for over one month were detected by pyrosequencing approach. The results implied that four AR-CpGs may be potential markers for age estimating.